Research progress of cell membrane biomimetic nanoparticles for circulating tumor cells - Zhang, Yingfeng; Wang, Jia (Frontiers in Oncology, 2024)
Early detection of cancer is crucial to reducing fatalities and improving patient outcomes. Metastasis is the first stage of aggressive cancers, often occurring before primary lesions can be seen. It occurs when cancerous cells disseminate to distant, nonmalignant organs through the bloodstream, known as circulating tumour cells (CTCs).CTCs, or cancer tumour cells, are valuable indicators for predicting treatment response, metastasis progression, and disease progression. However, they are primarily used for research due to challenges like heterogeneity, separation from blood, and lack of clinical validation. Only a few methods have been approved for clinical use. One area of research is the isolation and identification of CTCs, which could significantly impact early cancer detection and prognosis. Current technologies using whole blood samples use size, immunoaffinity, and density approaches, along with positive and negative enrichment techniques. Surface modification of nanomaterials is important for effective cancer therapies because it improves their ability to target and reduces interactions with healthy tissues. Consequently, researchers have created biomimetic nanoparticles covered with cell membranes using functional, targeted, and biocompatible coating technology. Nanoparticles with membranes can target specific cells, stay in circulation for longer, and avoid immune responses, which makes them much better at capturing CTCs. This study examines the current opportunities and difficulties associated with using cell membrane-coated nanoparticles as a capture technique for CTCs. In addition, we examine potential future developments in light of the current obstacles and investigate areas that require further research to fully understand its growing clinical possibilities.